-2(p+3q)-2(6p-7q)=0

Simple and best practice solution for -2(p+3q)-2(6p-7q)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(p+3q)-2(6p-7q)=0 equation:


Simplifying
-2(p + 3q) + -2(6p + -7q) = 0
(p * -2 + 3q * -2) + -2(6p + -7q) = 0
(-2p + -6q) + -2(6p + -7q) = 0
-2p + -6q + (6p * -2 + -7q * -2) = 0
-2p + -6q + (-12p + 14q) = 0

Reorder the terms:
-2p + -12p + -6q + 14q = 0

Combine like terms: -2p + -12p = -14p
-14p + -6q + 14q = 0

Combine like terms: -6q + 14q = 8q
-14p + 8q = 0

Solving
-14p + 8q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-8q' to each side of the equation.
-14p + 8q + -8q = 0 + -8q

Combine like terms: 8q + -8q = 0
-14p + 0 = 0 + -8q
-14p = 0 + -8q
Remove the zero:
-14p = -8q

Divide each side by '-14'.
p = 0.5714285714q

Simplifying
p = 0.5714285714q

See similar equations:

| 7a(1+b)-a(4+b)=0 | | 7a(1+b)-4a(4+b)=0 | | 2x*x=100 | | 11-3(x+5)-6x=0 | | f(x)=2x^2-9x-35 | | 11+25-5=2x-5 | | 5/9x15 | | 25/0.03 | | 5ln(a)-2=0 | | 2a+3b+4a=50 | | sqrt(21x+1)+sqrt(13x-1)=4 | | c=2a+3b+c | | 2(a+b)-5(2a-b)=0 | | -30x+2=-4x^2+5x+11 | | 4(x+3y)+3x=0 | | 2a-4b-a-6b=0 | | x^3-22x^2+73x=-242 | | 2a*-4b-a*-6b=0 | | -15x^2-14=0 | | 3x*(-3)=-9x | | -5x*2y+5y*3x=0 | | x^2+10x-5=-3x^2+2x | | 2*4x-3*3x=0 | | -20=-10r | | 3x^2-20=55 | | G=Q+Qrt | | 6+8x-10-9x=0 | | 12=6r | | -7a-b-3a-5b=0 | | 16x+21=-3x^2 | | 0=2x+cosx | | 4a+b-5a-3b=0 |

Equations solver categories